Correction: Two-test algorithms for infectious disease diagnosis: Implications for COVID-19. - Sunil Pokharel; Lisa J White; Jilian A Sacks; Camille Escadafal; Amy Toporowski; Sahra Isse Mohammed; Solomon Chane Abera; Kekeletso Kao; Marcela De Melo Freitas; Sabine Dittrich (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0000293.].